Intelligent 3D video avatar for immersive telecommunication - Lee, SY; Kim, IJ; Ahn, SC; Lim, MT; Kim, HG (SPRINGER-VERLAG BERLIN, 2005)
Immersive telecommunication is a new challenging field that enables a user to share a virtual space with remote participants. The main objective is to offer rich communication modalities, as similar as those used in the face-to-face meetings like gestures, gaze awareness, realistic images, and correct sound direction. Moreover, natural full body interaction is presented as a tangible interface where people meet the cyber space. As a result, the user can be immersed and has interaction with virtual objects including remote participants. This would overcome the limitations both of the conventional video-based telecommunication and also the VR-based collaborative virtual environment approaches.